2017
DOI: 10.1080/14763141.2017.1371216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the contribution of lower extremity kinetics to whole body power output during the power snatch

Abstract: This study evaluated the contribution of lower extremity (hip, knee and ankle) net joint torques (NJT) to whole body power (WBP) output during the power snatch (PS). Ten experienced weightlifters (five males and five females) performed five trials of the PS with 60% of one repetition maximum. Lower extremity NJT and WBP were extracted through a three-dimensional motion analyses and used for data analyses. Pearson correlation coefficients were obtained to observe the relationship between lower extremity NJT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This observation is supported by the calculations made by Bartonietz [15], which showed that during the performance of the snatch the power generated in the hip joint is more than 3 times greater than that generated in the knee joints. Similar results were reported by Lee et al [35], who investigated the power snatch in non-professional weightlifters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is supported by the calculations made by Bartonietz [15], which showed that during the performance of the snatch the power generated in the hip joint is more than 3 times greater than that generated in the knee joints. Similar results were reported by Lee et al [35], who investigated the power snatch in non-professional weightlifters.…”
Section: Discussionsupporting
confidence: 90%
“…During the power snatch, a lifter does not need to perform a full squat when receiving the bar [6,15,16], which makes it easier to execute than the snatch. For this reason, the power snatch is often used in the training of young weightlifters [24] and non-professional weightlifters [3536]. Higher values of coefficients γ 10 and γ 20 compared to those for the snatch indicate that mean increases in record scores in the power snatch occurred at a faster rate, and the trajectory of these records was more curved.…”
Section: Discussionmentioning
confidence: 99%
“…Two reflective markers were placed at each of the barbell's right and left ends, resulting in a total of four markers (Fig 1). In previous studies, the sampling frequency was at 200-250 Hz in the 3D motion analysis of snatch [1,5,16]. However, the body collides with the barbell during the second pull phase of the snatch [17].…”
Section: Methodsmentioning
confidence: 99%
“…To be able to successfully lift in the snatch and clean techniques or catch the barbell after the second pull, it is critical that the bar reaches a sufficient height in the second pull phase to provide a power output associated with sufficient speed to produce this height. A higher bar velocity is considered a distinctive feature of strong weightlifters [24][25][26][27], but previous studies showed that PV is not the only determining factor for successful versus unsuccessful weightlifting [26,28]. A successful lift cannot be predicted over a single variable, and it has been reported that the barbell trajectory, barbell velocity, barbell displacement, and method through which the force is applied to the barbell are closely related to a successful lift [29].…”
Section: Discussionmentioning
confidence: 99%